2D arbitrary lagrangian-eulerian (ALE) model of blood flow in the left ventricle of the heart / Zati Hakim Azizul Hasan - Zati Hakim, Azizul Hasan (2006)
This research is a study of the dynamics of the heart valves and the blood using numerical computational technique. This numerical technique is known as the Arbitrary Lagrangian-Eulerian (ALE) and is introduced in a finite element environment. By means of a mesh movement method, the ALE uses separate sets of reference systems to study the fluid-structure interaction of the heart. The fluid domain is most conveniently described with respect to an Eulerian reference frame while a Lagrangian formulation is more appropriate for the structure domain. Due to the incompatibility factor of the two reference frames, coupling of the reference systems is carried out on an arbitrary computational grid which allows numerical modeling of the blood motion and the mechanical valves under physiological conditions defined by governing constitutive formulation. The use of graphical simulation in a time step fashion is an essential aid in obtaining realistic physical representation of the dynamic interaction. Results from the experimental simulations in comparison to physiological data have been encouraging. This geometrically simplified model albeit with much constraints has the capability to derive plausible velocity pattern of the flow in relation to the periodicity mechanics of the mitral and aortic valves in two cardiac cycles.